Potentiality of Vygotsky’s Sociocultural Theory in Exploring the Role of Teacher Perceptions, Expectations and Interaction Strategies - Allahyar, Negah; Nazari, Ahmad (Working Papers in Language Pedagogy, 2012)
This article reviews Vygotsky’s sociocultural theory as one of the current frameworks in the study of learning and teaching processes. Arguing that learners’ interaction is vital for language learning in English as a Foreign Language (EFL) classrooms and that the teacher’s perceptions and expectations can foster or discourage this interaction, the article shows how the sociocultural model of learning can provide a suitable theoretical lens through which to explore EFL learner interaction. The literature shows that this interaction has been extensively explored in situ and various empirical reasons have been given for students’ willingness to communicate or for their reticence. However, EFL research gives scant attention to the theoretical angle of this practical aspect of the learning process. This article, therefore, seeks to address this lacuna by looking into a learning model that can be utilized as a theoretical lens for studying a practical aspect of EFL learning and teaching, namely EFL students’ engagement in classroom interaction.